Perancangan Quality Plan Produksi Genteng Beton dan Paving Block di CV Karya Utama - Edwin Tri Sulistyo (Jurnal Titra, 2021)
CV Karya Utama is a company in manufacturing and selling concrete roof tiles and paving blocks since 1986. Even though CV Karya Utama has been around for a long time, it does not have a quality control division. The problem at CV Karya Utama is that there is no structured quality plan so that many defective items are sent to customers. Therefore, the purpose of this final project is to make a quality plan for the production of concrete roof tiles and paving blocks CV Karya Utama. The method used to make a quality plan for concrete tiles and paving blocks is to take references from Standar Nasional Indonesia and use voice of customer to find out standards the customer wants. The result of this research is the quality plan of concrete roof tiles and paving blocks that can be used to improve the quality of the production of concrete roof tiles and paving blocks CV Karya Utama.